Multi-scale dynamic behaviors of oxygen entering carbon fiber/epoxy resin interfaces under thermal environment - Long, Jing (2023)
Understanding the thermo-oxidative ageing behavior of carbon fiber/epoxy resin interfaces at multiple scales is crucial for structural optimization and durable design of composites. Here we report the effects of oxygen entering the interface on the 3D ageing crack evolutions, interface spatial structures, and multi-scale dynamic mechanisms for carbon fiber/epoxy composites under a thermal environment using experiments and molecular dynamics (MD) simulations. The dynamic behaviors under ambient temperature environments were studied for comparison. Ageing cracks first appear at the interface and then spread to the surrounding resin-rich region as the ageing time increases. Interface cracks provide channels for oxygen to enter the interior of the composite. The MD results show that interface systems with fewer oxygen molecules have serious interface cracks, weaker interaction energies and stronger diffusion capabilities than those with more oxygen molecules. The oxygen amounts entered the interface and the intermolecular interactions affect the interface dynamic behaviors. High temperature promotes the molecular movement, accelerates the interface cracking, weakens the interaction energy, and improves the diffusion capability. The diffusion of oxygen molecule from the interface to the epoxy matrix is a gradual process and is affected by the interface cracks.